Social protection in the conditions of modernization of the Kazakhstan society (The Journal of Psychology and Sociology, 2012)
In the conditions of prompt change of public life under the influence of formation of market society the appeal to experi- ence of the developed countries which have created effectively operating social sphere within developed market society is justifiable. The social sphere is the key sphere of society. Formation of civil society and the social state is an actual problem in modern conditions. Studying of experience of the developed countries allows to choose among all existing models of eco- nomic development the most acceptable options for the purpose of their application in practice and the effective solution of strategic tasks in the field of the social sphere of the Kazakhstan society.
Keywords: social protection; upgrading the model; the Kazakh society.